Effect of Graviola (Annona Muricata l.) and Ginger (Zingiber Officinale Roscoe) on Diabetes Mellitus Induced in Male Wistar Albino Rats - Al Syaad, K M; Elsaid, F G; Abdraboh, M E; Al-Doaiss, A A (Folia biologica, 2019)
Annona and ginger have prominent uses in traditional medicine; their therapeutic properties have not been sufficiently explored. The ameliorative effect of Annona or ginger extracts on hyperglycaemia associated with oxidative stress, inflammation, and apoptosis in experimentally induced diabetes was addressed. Type 1 diabetes in male rats was induced by a single injection of streptozotocin (STZ; 40 mg/kg, i.p.), then Annona (100 mg/kg) or ginger (200 mg/kg) extracts were orally administered daily for 30 days. The Annona and ginger extracts ameliorated hyperglycaemia, insulin level, glycosylated haemoglobin (HbA1c) and insulin resistance (HOMA-IR) levels in the diabetic rats. The treatments significantly ameliorated liver function enzymes and total proteins; this was confirmed by histopathological examination of liver sections. Annona and ginger extracts significantly reduced elevated malondialdehyde (MDA) and restored activity of antioxidant enzymes in the liver such as glutathione peroxidase (GPx), glutathione reductase (GR), superoxide dismutase (SOD), and catalase (CAT) and the hepatic content of reduced glutathione (GSH). The oxidative stressdependent inflammation was regulated by both Annona and ginger extracts, which was indicated by down-regulation of TNF-α, NF-κB, pro-apoptotic proteins Bax, p53, and anti-apoptotic protein Bcl-2. Moreover, the expression of insulin receptor (INSR) and glucose transporter 2 (GLUT2) genes was markedly regulated by both these extracts. The results suggest that Annona and ginger extracts ameliorate the hepatic damage resulting from diabetes by advocating antioxidants and modulating apoptotic mediator proteins in the liver of diabetic rats. In conclusion, Annona and ginger extracts have a potential therapeutic effect in the treatment of diabetes and its complications.
Keywords: NF-kappa B; Zingiber officinale; antioxidancia; mužské pohlaví; oxidační stres; Male; Plant Extracts; protein X asociovaný s bcl-2; Apoptosis; Glucose Transporter Type 2; Insulin Resistance; regulace genové exprese; Glycated Hemoglobin; Oxidative Stress; nádorový supresorový protein p53; Antioxidants; Receptor, Insulin; Gene Expression Regulation; bcl-2-Associated X Protein; TNF-alfa; Insulin; Glycated Hemoglobin A; potkani Wistar; inzulinová rezistence; jaterní testy; malondialdehyd; přenašeč glukosy typ 2; játra; experimentální diabetes mellitus; Malondialdehyde; Tumor Necrosis Factor-alpha; rostlinné extrakty; Animals; zázvor lékařský; Biomarkers; apoptóza; biologické markery; zvířata; inzulin; receptor inzulinu; glykovaný hemoglobin; Rats, Wistar; Tumor Suppressor Protein p53; Diabetes Mellitus, Experimental; Liver; Annona; Liver Function Tests; Blood Glucose; krevní glukóza